The Influence of Online Advertising on Sales in the Marketplace - Pereira, Lucas (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the influence of online advertising on marketplace sales. The approach used in this study is a quantitative approach with an explanatory research type. The population in this study was business actors who actively use advertising features on marketplace platforms, with a purposive sampling technique. Data were collected through questionnaires and sales report documentation, then analyzed using simple linear regression, t-test, and coefficient of determination. The results show that online advertising has a positive and significant effect on marketplace sales. This is evidenced by a significance value smaller than 0.05 and a positive regression coefficient value. In addition, the effectiveness of online advertising is also reflected in increased impressions, click-through rates (CTR), and sales conversion rates. This study concludes that optimizing digital advertising strategies can improve sales performance sustainably if supported by product quality, competitive prices, and good service.